2020
DOI: 10.1590/pboci.2020.141
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Calcium Hydroxide on Human Umbilical Cord Mesenchymal Stem Cells

Abstract: To examine the cytotoxicity of calcium hydroxide on human umbilical cord mesenchymal stem cells (HUCMSC) to understand the characteristics for use in regenerative dentistry procedures especially regenerative endodontics. Material and Methods: HUCMSC was isolated, cultured, and confirmed by flow cytometry. The biological characteristics, such as cell morphology, proliferation, and protein expression, were screened. To check the cytotoxicity, HUCMSC was cultured and divided into two groups, the control group (cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…3 MSCs have been successfully extracted from various tissues, such as the umbilical cord, hair follicles, and adipose tissue, including orofacial tissues. [4][5][6][7][8] MSCs can be derived from orofacial tissue, including the dental pulp of permanent or deciduous teeth, the periodontal ligament, and the gingiva. [9][10][11][12][13] One of the potential and superior sources of MSCs from the oral cavity was in the gingiva.…”
Section: Introductionmentioning
confidence: 99%
“…3 MSCs have been successfully extracted from various tissues, such as the umbilical cord, hair follicles, and adipose tissue, including orofacial tissues. [4][5][6][7][8] MSCs can be derived from orofacial tissue, including the dental pulp of permanent or deciduous teeth, the periodontal ligament, and the gingiva. [9][10][11][12][13] One of the potential and superior sources of MSCs from the oral cavity was in the gingiva.…”
Section: Introductionmentioning
confidence: 99%
“…The alkali condition from calcium hydroxide would impact the surrounding tissues, including healing, anti-inflammation 17 and cytotoxic, leading to apoptosis. 18,19 The result of this study showed a significant difference between CH-iodophors and CH-barium sulfate. The ability of CH-iodophors to inhibit E. faecalis and P. gingivalis growths is significantly greater than that of the CH-barium sulfate root canal dressing.…”
Section: Enterococcus Faecalis and Porphyromonas Gingivalismentioning
confidence: 63%
“…Pulp-capping treatment with calcium hydroxide is said to be successful if calcium hydroxide can dissociate into ionic forms Ca 2 + and OH -. 15 This is an ionization process in tissues that explains the antibacterial properties of calcium hydroxide. The dissociation of calcium hydroxide into Ca 2 + and OHdepends on the carrier that is used.…”
Section: Discussionmentioning
confidence: 99%